Poisoned wells : accusations, persecution, and minorities in medieval Europe, 1321-1422 - Barzilay, Tzafrir (Middle Ages series., 2022)
"Between 1348 and 1350, Jews throughout Europe were accused of having caused the spread of the Black Death by poisoning the wells from which the entire population drank. Hundreds if not thousands were executed from Aragon and southern France into the eastern regions of the German-speaking lands. But if the well-poisoning accusations against the Jews during these plague years are the most frequently cited of such cases, they were not unique. The first major wave of accusations came in France and Aragon in 1321, and it was lepers, not Jews, who were the initial targets. Local authorities, and especially municipal councils, promoted these charges so as to be able to seize the property of the leprosaria, Tzafrir Barzilay contends. The allegations eventually expanded to describe an international conspiracy organized by Muslims, and only then, after months of persecution of the lepers, did some nobles of central France implicate the Jews, convincing the king to expel them from the realm. In Poisoned Wells Barzilay explores the origins of these charges of well poisoning, asks how the fear took root and moved across Europe, which groups it targeted, why it held in certain areas and not others, and why it waned in the fifteenth century. He argues that many of the social, political, and environmental factors that fed the rise of the mass poisoning accusations had already appeared during the thirteenth century, a period of increased urbanization, of criminal poisoning charges, and of the proliferation of medical texts on toxins. In studying the narratives that were presented to convince officials that certain groups committed well poisoning and the legal and bureaucratic mechanisms that moved rumors into officially accepted and prosecutable crimes, Barzilay has written a crucial chapter in the long history of the persecution of European minorities."--